Penanganan Diare Menggunakan Metode BRAT (Bread, Rice, Applesauce, Toast) di Wilayah Kerja Puskesmas Pauh: Diarrhea Treatment Using the BRAT Method (Bread, Rice, Applesauce, Toast) in the Pauh Public Health Centre Area - Muthmainnah, Muthmainnah; Sari, Ira Mulya; Ananda, Yuanita; Sidaria, Sidaria; Khairina, Ilfa; Murni, Dewi; Nelwati, Nelwati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The educational and socialization activities conducted on September 13, 2023, aimed to increase community knowledge about diarrhea and its home management. Diarrhea is a common health problem among children under 3 years old in developing countries, with an average of 3 episodes per year. Each episode of diarrhea can cause children to lose the necessary nutrients needed for growth, making it the leading cause of malnutrition in children and the second leading cause of death after pneumonia. One recommended dietary method for managing acute diarrhea is the BRAT Diet, which consists of Bananas, Rice, Applesauce, and Toast. This diet helps reduce the workload on the digestive system and provides easily digestible foods. This educational activity targeted mothers with toddlers in the working area of Pauh Community Health Center. The program was implemented through counseling using PPT media and distributing leaflets to the participants. The activity was evaluated using pretests and posttests to measure the increase in community knowledge. The evaluation results showed an increase in community knowledge after the educational and socialization activities were conducted. This program highlights the importance of education and socialization in enhancing community knowledge about home management of diarrhea, which can ultimately help reduce the rates of malnutrition and child mortality.